2006
DOI: 10.1017/s1041610205002966
|View full text |Cite
|
Sign up to set email alerts
|

Successful aging in Shanghai, China: definition, distribution and related factors

Abstract: The rate of successful aging in Shanghai, China is similar to that found in studies from western countries. There are some potentially modifiable factors that may relate to successful aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
72
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 14 publications
11
72
3
1
Order By: Relevance
“…In a study of factors associated with the maintenance of exceptional good health in old age, Kaplan et al (46) found that in a 10 year follow-up “thrivers” were more likely at baseline to have: higher income, lower psychological distress, never smoked, and moderate alcohol use. Our longitudinal findings may indicate causal factors underlying the earlier cross-sectional studies reporting associations between composite measures of successful aging and lifestyle factors, particularly not smoking, as influences in aging well (47, 48). …”
Section: Discussionmentioning
confidence: 53%
“…In a study of factors associated with the maintenance of exceptional good health in old age, Kaplan et al (46) found that in a 10 year follow-up “thrivers” were more likely at baseline to have: higher income, lower psychological distress, never smoked, and moderate alcohol use. Our longitudinal findings may indicate causal factors underlying the earlier cross-sectional studies reporting associations between composite measures of successful aging and lifestyle factors, particularly not smoking, as influences in aging well (47, 48). …”
Section: Discussionmentioning
confidence: 53%
“…The MMSE correlates well with a number of cognitive screening tests and neuropsychological tests [4]. The Chinese version of the MMSE has reasonable sensitivity and specificity [15, 16]. The MMSE consists of 12 scores: a Total Score and 11 Index Scores.…”
Section: Methodsmentioning
confidence: 99%
“…They found education, better housing, social network and support, spirituality, and nutrition to be salient factors associated with successful aging. A study using a similar definition of successful aging in a community-based sample of Chinese elders in Shanghai, China found gender, age, marital status, and engagement in leisurely activities to be associated with successful aging (Li, et al, 2006). Using a confirmatory factor analysis, Ng et al (2011) found caring and productive forms of engagement to be better predictors than illness avoidance and functioning of successful aging.…”
Section: Introductionmentioning
confidence: 99%